The Influence of Investment Knowledge and Risk Perception on Generation Z Investment Decisions with Technological Advancement as a Moderating Variable - Felisia Angreyani; Manuel August Todingbua; Benyamin Mongan (Journal of Marketing Management and Innovative Business Review, 2025)
This study aims to examine and obtain empirical evidence regarding the influence of investment knowledge and risk perception on the investment decisions of Generation Z, with technological advancement as a moderating variable. This research uses a quantitative approach with data analysis through the Partial Least Squares (PLS) 4.0 method. The research data consists of primary data collected through online questionnaires using Google Forms distributed via WhatsApp, as well as secondary data obtained from previous research. The study population consists of students of the Faculty of Economics and Business, Paulus Makassar Indonesian Christian University, aged 18-23 years, who have invested in the capital market. A sample of 30 respondents was selected using non-probability sampling with a purposive sampling technique. The results show that Investment Knowledge and Risk Perception have a positive effect on Investment Decisions. Meanwhile, technological advancement as a moderating variable does not strengthen or weaken the influence of investment knowledge and risk perception on the investment decisions of Generation Z.